The effect of agroecological condition of production on indicator for viability of potatoes seed-tubers - Poštić D.; Sabovljević Radovan; Ikanović Jela; Davidović Marija; Goranović Đ. (Selekcija i Semenarstvo, 2007)
Investigation have been presents an contribution to researching of controlled and non-controlled factors on viability of potatoes seed-tubers. Also, in way of metodology brushing, measuring and estimation of parameters of life viability of potato seed-tubers (characteristic). Researches have been done on potato seed-tubers of Desiree and Kondor cultivars. Seed material of two generation is comprised: Original and ICR. Experimental production of seed material have been done during two year vegetation period (2000 and 2001) on three location (Kotraza, Sjenica, Golija). Keeping of seed-tuberss in cold condition lasted about 100 days. Then seed-material has been exposed to thermal induction. After thermal induction and cutting of apical germ of tuber, material have been exposed to dark and light phase with adequate temperature regimes. Following characteristics were brushing and measured on (seed-tubers): number of germ per tuber, germ length per tuber, germ plumpness per tuber, number of leaves per tuber. Characteristics of seed-tubers have been researched from 7 day after beginning of dark phase. Characteristics such as number of germ, germ length and germ plumpness were researching on 7th and 14th days (in dark phase) and 21st, 28th and 35th days (in light phase). Number of leaves were researching 21st, 28th and 35th days (in light phase). Previously, seed material has been controlled on healthy state. Experimental data are calculated with three factorial analyze variance (for factors: seed category, production location and year-vegetation period) for each cultivar separately and for each term of characteristics brushing. Among cultivars clear and large difference are sawn in the way of seed value characteristics as different statistical significance of factor and interaction for number of germ, length of germ and plumpness of germ. For the characteristic number of leaves per tuber there is no statistical significance for none of factor or interactions at both cultivars in all three terms. Results are applicable in seed-tubers production of cultivars Desiree and Kondor. .